Experimental Investigation of 2nd Generation Bioethanol Derived from Empty-fruit-bunch (EFB) of Oil-palm on Performance and Exhaust Emission of SI Engine - Yanuandri Putrasari; Haznan Abimanyu; Achmad Praptijanto; Arifin Nur; Yan Irawan; Sabar Pangihutan Simanungkalit (National Research and Innovation Agency, 2014)
The experimental investigation of 2nd generation bioethanol derived from EFB of oil-palm blended with gasoline for 10, 20, 25% by volume and pure gasoline were conducted on performance and exhaust emission tests of SI engine. A four stroke, four cylinders, programmed fuel injection (PGMFI), 16 valves variable valve timing and electronic lift control (VTEC), single overhead camshaft (SOHC), and 1,497 cm3 SI engine (Honda/L15A) was used in this investigation. Engine performance test was carried out for brake torque, power, and fuel consumption. The exhaust emission was analyzed for carbon monoxide (CO) and hydrocarbon (HC). The engine was operated on speed range from1,500 until 4,500 rev/min with 85% throttle opening position. The results showed that the highest brake torque of bioethanol blends achieved by 10% bioethanol content at 3,000 to 4,500 rpm, the brake power was greater than pure gasoline at 3,500 to 4,500 rpm for 10% bioethanol, and bioethanol-gasoline blends of 10 and 20% resulted greater bsfc than pure gasoline at low speed from 1,500 to 3,500 rpm. The trend of CO and HC emissions tended to decrease when the engine speed increased.